Hubungan Estrus dan Deposisi Semen terhadap Persentase Kebuntingan pada Kerbau - Yendraliza; Busro (Jurnal Peternakan Mahaputra, 2021)
This study aimed to determine the emergence of post-synchronization estrus, cement deposition during Artificial Insemination (IB) and the number of buffalo pregnancy in Kampar District. The hormones used in this study were PGF2α and GNRH. The Chi Square used as analysis data method with variables measured were cement deposition (4th, 2nd cervical ring), buffalo pregnancy (number of pregnant; not pregnant) and estrus (buffalo estrus; not estrus). The results showed that the percentage of post-synchronous estrous buffalo was 84.61% and postsynchronized buffalo cattle which was not estrous was 15.39%. Chi Sqaure analysis for estrus on pregnancy was X²count> X²table (9.4545> 3.841) and cement deposition on pregnancy was X²count> X²table (40.7524> 3.841). Theresults of this study indicated that estrus synchronization in buffalo in Kampar Regency was able to produce estrus up to 84.61%. The post-synchronous estrus also showed a significant relationship with the number of pregnancies. The cement deposition on the 4th cervical ring also has a significant relationship with the number of buffalo pregnancy in Kampar District.